Discovery of brussonol analogs as lead candidates for malaria - Barbosa, Camila de Souza (2024)
Malaria is a disease caused by Plasmodium parasites affecting millions of people globally. Different strategies were applied throughout the years to decrease malaria burden, however the emergence of resistance parasites to antimalarials, especially related to artemisinin, threatens the progress achieved so far towards control, prevention, and elimination of the disease. In this sense, new antimalarials are critically needed, and natural products constitute an interesting source of new chemical scaffolds. A phenotypic screen identified brussonol (1) (IC50 = 16 μM) as a promising antiplasmodial candidate. Structure optimization resulted in analogs 3-fold (IC50 ~ 5 μM) more potent than brussonol. Further experiments determined that this chemical series shows a fast-acting inhibition, no cross-resistance with standard antimalarials, and potent inhibitory activity against P. knowlesi laboratory-based, P. falciparum and P. vivax clinical isolates. Moreover, brussonol displayed an additive profile when combined in vitro with artesunate. Molecular mode of action (MoA) studies indicated that brussonol derivatives disrupt Ca2+ homeostasis, but do not inhibit PfSERCA. Exposing isolated trophozoites to a brussonol derivative (compound 8) resulted in hyperpolarization of the parasites plasma membrane. In this sense, additional experiments are required to determine how compound 8 disrupts membrane potential. For example, applying genetic reverse methods in Toxoplasma gondii parasites, coupled to compound treatment, might help uncover this series MoA. Thus, T. gondii could be used as a model organism because the inhibitory effect of compound 8 (IC50 = 2.2 ± 0.2 μM) on this apicomplexan was demonstrated. In summary, the identification and characterization of brussonol as a new scaffold possessing promising antiplasmodial activity support the development of new derivatives with enhanced properties, aiming to discover new lead candidates for combating malaria.